The reasonably prudent person, or me?. Issue 5 (15th March 2020) - Simpson, Ain; Alicke, Mark D.; Gordon, Ellen; Rose, David
Abstract: Abundant research concerning the role of the self in social judgment suggests that people have a strong tendency to evaluate others' actions, preferences, and values with regard to their own. Reliance on self‐standards contrasts with the legal standard of the reasonably prudent person (RPP) standard, which presumably represents the behavior of the average person in the community. In three studies that investigated judgments of harmful actions, we compared the influence of self‐standards ("How likely would I behave in this manner?") and RPP estimates ("How likely would the average, reasonable person in the community behave in this manner?"). In each study, self‐standards influenced participants' judgments of guilt and the acceptability of the defendant's actions more than did judgments about what a RPP would do. Studies 2a and 2b also investigated attitudinal differences in susceptibility to RPP consensus manipulations. Participants judged a target who committed murder in self‐defense, and also projected their own hypothetical behavior in the scenario. When the manipulated RPP disapproved of the murder, the target was deemed more culpable, but only among participants who themselves were unwilling to commit the hypothetical act. Participants who expressed willingness to murder in self‐defense were unaffected by RPP information, regardless of whether or not it was consistent with their own stance. Hence, RPP information at best exerted minimal influence on juridical judgments, and only among certain participants. Implications of these findings for legal applications of the RPP, and for the role of the self in social judgment, are discussed.